Environmental and Anthropogenic Influences on Coliform Concentrations in the Octopus insularis Production Chain in the Veracruz Reef System, Gulf of Mexico - Sarai Acuña-Ramírez; María de Lourdes Jiménez-Badillo; Gabriela Galindo-Cortes; Angel Marval-Rodríguez; María del Refugio Castañeda-Chávez; Christian Reyes-Velázquez; Hectorina Rodulfo-Carvajal; Marcos De Donato-Capote (Animals, 2023)
Coliforms are relatively common in aquatic environments, but their concentrations can be increased by environmental changes and anthropogenic activities, thus impacting fisheries resources. To determine the microbiological quality in the octopus production chain (capture, post-capture, processing and commercialization), total (TC) and fecal (FC) coliforms were quantified in sea water, fresh octopus, fresh water, ice and octopus in two presentations: packed in ice and boiled. Samples came from fishing zones Enmedio, Chopa and La Gallega at the Veracruz Reef System (VRS) during dry, rainy and windy seasons. The coliforms were determined using the most probable number technique (MPN). The most relevant results indicated that octopus packed in ice coming from the commercialization stage had FC levels >540 MPN/100 g, which exceeded the permissible limits (230 MPN/100 g). Therefore, these products present a risk for human consumption. Differences in FC were observed in octopuses between the three fishing zones (H = 8.697; p = 0.0129) and among the three climatic seasons, increasing during the rainy season, highlighting La Gallega with 203.33 ± 63 MPN (H = 7.200; p = 0.0273). The results provide evidence of the environmental and anthropogenic influences on coliform concentrations and the urgent need to implement an efficient cold chain throughout octopus production stages with adequate handling practices to reverse this situation.